AIoT Technologies and Applications for Smart Environments - Alazab, Mamoun (Institution of Engineering & Technology, 2023)
In this edited book, the authors present the challenges, technologies, applications and future trends of the artificial intelligence-enabled internet of things (AIoT) in realizing smart and intelligent environments
Description based on publisher supplied metadata and other sources